2008
DOI: 10.2478/fhort-2013-0110
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nitrogen form and air temperature during foliar fertilization on gas exchange, the yield and nutritive value of spinach (Spinacia oleracea L.)

Abstract: A pot experiment conducted in a growth chamber studied the effectiveness of foliar fertilization of spinach (Spinacia oleracea L.), with different forms of nitrogen applied with the air temperatures: 5°C, 15°C and 25°C. Nitrogen was supplied three times in the form of 1% water solutions of CO(NH 2 ) 2 , NH 4 NO 3 , NH 4 HCO 3 and Ca(NO 3 ) 2 × 4 H 2 O, with water as the control. The obtained results showed that nitrogen in the form of Ca(NO 3 ) 2 × 4 H 2 O -independent of the air temperature during solution ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Chlorophyll concentration is influenced by environmental factors and N fertilization (Barickman and Kopsell, 2016) and the form and ratio of N in plants (Borowski and Michalek, 2008). Previous research demonstrated that higher ratios of NO 3 − -N to NH 4 + -N positively influenced chlorophyll concentrations in the leaf tissue of kale (Brassica oleracea L. var.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll concentration is influenced by environmental factors and N fertilization (Barickman and Kopsell, 2016) and the form and ratio of N in plants (Borowski and Michalek, 2008). Previous research demonstrated that higher ratios of NO 3 − -N to NH 4 + -N positively influenced chlorophyll concentrations in the leaf tissue of kale (Brassica oleracea L. var.…”
Section: Discussionmentioning
confidence: 99%
“…In times of restricted nutrient uptake from soil, foliar fertilization results in a higher N uptake efficiency compared to soil‐applied fertilizers (Krishnasree et al., 2021; Singh et al., 2013). Even small quantities of aerially applied urea or ammonium (NH 4 + ) may promote growth and green coloration of spinach leaves as indicated by the results of a greenhouse fertilization trial (Borowski & Michalek, 2008). On the other hand, foliar sprays can lead to necrosis on leafy vegetables (Krishnasree et al., 2021; Singh et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Up to a certain point, N fertilizer has a positive effect on plant productivity (Borowski and Michałek, 2008). Increased N use is almost always associated with high nitrate accumulation, especially in leafy vegetables (Premuzic et al, 2004;Santamaria, 2006;Prasad and Chetty, 2008;Fallovo et al, 2009;Saleh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%